Apicoectomy and root canal treatment of a maxillary right central incisor with discoloration, class IV ellis fracture, and radicular cyst - Elitasari, Denti; Wijaya, Meliana Ganda; Kristanti, Yulita; Mulyawati, Ema (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
In cases of pulp necrosis, infection products can spread into the periapical tissues, triggering an inflammatory response that stimulates the proliferation of the epithelial cell rests of Malassez. As the epithelial mass enlarges, the central cells—farther from the nutritional supply, undergo necrosis, leading to fluid accumulation. The cyst continues to expand due to cyst wall proliferation and increased hydrostatic pressure in the lumen. This pressure causes the accumulated fluid to spread and compress the epithelial lining of the fibrous capsule. This report presents the successful management of a radicular cyst in the maxillary anterior region through apicoectomy. The patient, who sustained a traumatic injury and fractured the tooth at the age of 10, later experienced pain and gingival swelling. Clinical examination revealed a Class IV Ellis fracture and discoloration of tooth 11. Radiographic evaluation showed a well-defined, rounded radiolucency approximately 20 mm in diameter in the periapical region of teeth 11 and 12, extending toward tooth 13. The treatment plan included disinfection and healing enhancement (DHE), root canal therapy, apicoectomy, and intracoronal bleaching. Apicoectomy proved to be a reliable treatment with a favorable prognosis for anterior teeth.